An exploratory study : Māori children's bi/literacy experiences moving from a kōhanga reo setting to a kura kaupapa Māori, bilingual, and mainstream education setting : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Education in Education Psychology at Massey University, Manawatu, New Zealand - Rona, Sarika (Massey University, 2015)
This research explored the bi/literacy experiences of three kōhanga reo children as they start school in one of the three school settings: kura kaupapa Māori, bilingual unit, and mainstream. A Kaupapa Māori approach underpinned this research and guided the case study methodology employed. Parents and teachers are interviewed to gain insight into the aspirations and expectations of their child’s literacy development. The children’s literacy experiences were observed in the school classroom upon school entry. The findings of each case study is discussed and analysed separately and then synthesised and critiqued. Key findings include the importance of home literacy support, relationship building, building on prior literacy experiences and knowledge, and quality language instruction in supporting biliteracy development. The study highlights the obligation for further understanding of biliteracy learning in New Zealand schools by teachers and parents, the need for more bilingual teachers, the urgency for further development of assessment tools appropriate for bilingual children, and the demand for quality resources that support literacy development in all school settings, kōhanga reo, and the home.
Keywords: Maori children; Education; Bilingual education; Literacy; New Zealand; Mōhio ki te kōrero pukapuka; Kura kaupapa Maori; Kōhanga reo